Tunisia : Employment Strategy, Volume 2. Annexes - World Bank (Washington, DC, 2013)
In spite of the Government's commitment to social development, with employment resting at the heart of Tunisia's Tenth Development Plan, the recent economic slowdown however, hampers expectations on meeting the employment goals of the Plan. Output growth would have to increase significantly in light of unchanged employment elasticity, to create enough jobs to absorb the increasing labor force. However, the Tunisian private sector has not played a dynamic role in terms of job creation: small and medium scale enterprises (SMEs), are mainly concentrated in the traditional manufacturing sectors, with low value-added; enterprise restructuring has not occurred, mainly due to an economic growth that has not led to enough reallocation of resources, despite the unexploited productivity gains in respect to reallocation of labor to high productivity sector; and, the high unemployment rates among educated youth, reflect gaps between skills in demand by employers, and skills offered by job seekers. Within this context, this report proposes broad policy options to help improve the country's employment strategy over the medium term. Several reforms - liberalization of the product markets, improvement of investment climate, and reforms in education and vocational training - have been implemented to improve labor market performance. The overall employment strategy needs to be based on the fundamentals of sound economic policies that promote competitive product markets, and private-sector-led growth, particularly in service industries. This will require an investment climate, and a favorable business environment, particularly for SME development, to promote both employment and productivity growth in high value-added sectors. Notwithstanding, investment policies should provide a better balance between utilization of capital and labor. And, regardless of its engagement to investments in human resources, Tunisia should ensure that ongoing reforms in education, and vocational training focus on market needs. Finally, labor market regulations and institutions need to be flexible, so as to adjust to changes in business conditions. This approach requires a more effective social protection system, through efficient active labor market programs and, perhaps, through income support for laid-off workers.